Keefektifan Media Hyperdoc Diferensiasi untuk Meningkatkan Pemahaman Materi Toleransi - Umi Rosidah (Jurnal Didaktika Pendidikan Dasar, 2024)
Implementing differentiated learning by utilizing technology is still a problem for teachers. This research aims to determine the effectiveness of using hyperdoc media in content differentiated learning by assessing initial learning through learning interest. This media development uses the ADDIE model which is then tested with a media feasibility test and media effectiveness test using the N-Gain Hake formula. The subjects of this research were 35 class 9B students. The research results show that the results of the media effectiveness test reached a score of 69.4 which is in the quite good category. It can be concluded that this differentiated hyperdoc media is effective in increasing students' understanding of tolerance material.